The software software engineers. (Economist, 2021)
The article informs that artificial intelligence is transforming the way computer programs are written. It mentions about the use of Generative Pre-Trained Transformer 3 an autoregressive language model that uses deep learning to produce human-like text by business enterprises such as Microsoft, and Tabnine.